Finance and Development, June 2003. (Finance and Development; Finance and Development ;, 2003)
This paper describes the importance of luck, timing, and political institutions in beating inflation. The paper highlights that countries experiencing high inflation typically make several disinflation attempts, some of which succeed only temporarily. If a country trying to stabilize prices and wages is unlucky enough to be exposed to severe external shocks-for example, a decline in demand for its exports-during its disinflation, the likelihood of failure is increased. A shock such as an increase in U.S. interest rates makes failure more likely for a country with an open capital account.